MINERAL RESOURCES IN RUSSIAN AND WORLD ECONOMY ARTICLE 1. RUSSIAN AND WORLD MINERAL RESOURCES SECTOR - Y. A. Kozlovsky (Известия высших учебных заведений: Геология и разведка, 2015)
On the basis of economic criteria analysis of different countries all over the world it is shown that their economies are connected to mineral resources, abilities of the countries to build independent politics. It is concluded that the absence of a smart and scientifically based state development strategy and of the exploitation of mineral resources sector based on the self-production pattern with a necessary part of export and restricted import threatens the national security of Russia and leads to the loss of geopolitical priorities in the world mineral resources sector. A number of measures for a crucial breakdown in the state policy in the field of geological subsoil study, in mineral resources reproduction and in directing geological researches are offered. Working out the concept of a new Federal Subsoil Law one should be guided by the main principle - the economic security of the country.